THE PHARMACOLOGY OF C PALLIDA I VASOCONSTRICTOR AND CLOTTING PROPERTIES - PEREZ CICERA, RAMON (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1944)
A brief account of the agriculture and plant resources of Mexico
GAC MED MEX
Keywords: PHARMACOLOGY, PALLIDA, VASOCONSTRICTOR, CLOTTING, PROPERTIES; CIENCIAS MEDICAS; FARMACOLOGIA; FITOFARMACOS